Rekonstruksi Sistem Pendidikan Islam Pada Masa Kerajaan Aceh Di Pulau Sumatra Abad Ke XVI-XVII - Fatimah Fatimah; Zahra Fil Jannah; Andis Andis; Idrus L (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study reconstructs the Islamic educational system in the Aceh Sultanate during the sixteenth and seventeenth centuries by employing a non-empirical library research design grounded in critical historiography. The analysis integrates historical, educational, and sociological approaches to examine institutional structures, epistemological foundations, and socio-political relations shaping educational practices. The findings reveal a multilayered system characterized by structured institutional networks, coherent knowledge transmission, and a strong integration between religious authority and political power. Educational practices functioned not only as mechanisms of knowledge dissemination but also as instruments for social reproduction and political legitimation. The curriculum reflected a synthesis of transmitted and rational sciences, supported by dialogical and evaluative pedagogical methods rooted in classical Islamic traditions. Furthermore, the system was embedded within broader socio-economic and intellectual networks, enabling Aceh to emerge as a significant center of Islamic scholarship in Southeast Asia. These findings contribute to contemporary discourse on Islamic education by offering a historically grounded model of integrated, adaptive, and contextually responsive educational systems.